ANALISIS KINERJA BELANJA DAERAH DALAM LAPORAN REALISASI ANGGARAN (LRA) BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN SUKABUMI - Siti Amelia (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to analyze the performance of regional expenditures on the Budg-et Realization Report (LRA) at the Regional Financial and Asset Management Agency of Sukabumi Regency. The research method used is descriptive qualitative analysis technique. The popu-lation in this study is the entire Budget Realization Report (LRA) at the Regional Finan-cial and Asset Management Agency of Sukabumi Regency for the 2018-2020 period. And the sample used is the Budget Realization Report (LRA) for the 2018-2020 period. The sampling method used is nonprobability with purposive sampling technique using data analysis consisting of; Regional Expenditure Variance Analysis, Regional Expenditure Growth Analysis, Regional Expenditure Harmony Analysis, Regional Expenditure Effi-ciency Ratio Analysis. For data collection used are observation, interviews, and docu-mentation. From the results of the study, it was found that the performance of Sukabumi district expenditure in terms of realization was stated to be running well. However, there is still a need for more optimization and improvement in terms of the use of the budget by the Regional Financial and Asset Management Agency.